Evolutionäre Politische Ökonomie: Inhalt und Methode - Hanappi, Hardy; Wäckerle, Manuel (Wirtschaft und Gesellschaft, 2014)
What is “evolutionary political economy”? Throughout all kinds of social sciences there exists no clear-cut definition, not even a commonly shared vision. This article presents a rather ambitious and non-ambiguous positioning of this discipline to fill this gap. It does so by characterizing its content, i.e. its object of investigation, as well as the languages (including formal languages) it uses. Since such a task also implies the necessity to draw the borders that distinguish the field from a multitude of new and fashionable economic schools the article also provides some essential demarcation lines – mostly they are rooted in the historical development of economic theories in their interplay with socioeconomic reality. With respect to the history of social theories our approach can probably be interpreted as an update of classical political economy with the help of most advanced formal techniques. Despite our focus on a unique, understandable, and operational definition of “evolutionary political economy” – sometimes using daring hypothesis – it is evident that like any theoretical innovation our proposal is meant to provoke the economic mainstream and thus will certainly have to undergo several changes to win this fight.